Tijdens een verblijf in Havana van 10-18 januari 1980. V.l.n.r. : Montane Oropesa, Choloma, Hoekstra, Castro, De Boo
Tijdens een verblijf in Havana van 10-18 januari 1980. V.l.n.r. : Montane Oropesa, Choloma, Hoekstra, Castro, De Boo.